ANALISIS DAN EVALUASI USER ACCEPTANCE DENGAN PENDEKATAN TECHNOLOGY ACCEPTANCE MODEL (TAM) PADA E-PROCUREMENT DI KABUPATEN KEBUMEN - , MOCH NASIR; , Widyawan, S.T., M.Sc., Ph.D. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
Implementation of e-procurement in the mechanism of procurement on Kebumen government regency makes a change from a manual system with a pattern into the form of face to face towards electronic services. The policy raises the attitude and behavior of users to accept the application and use it for real. This study aims to obtain empirical evidence about the effect of acceptance aspects of convenience (ease of use) and utility (usefulness) understanding of computers and the Internet on e-procurement in Kebumen handle links by using a model approach to technology acceptance model (TAM). Analysis stuctured equation modeling (SEM) was used to determine the relationship between exogenous variables to endogenous variables with the help of AMOS software. Evaluation of analysis results are used as ingredients making technical recommendations, practical as well as regulations on e-procurement, so that the goals and objectives of the implementation of these policies can be achieved.